The Effect of Problem-Based Learning Assisted by The Desmos Application on Students’ Mathematical Ability in Quadratic Function Material - Hetty Elfina; Izwita Dewi; Hamidah Nasution (MASI Mandiri Edukasi, 2026)
Problem-based learning is one instructional model that can be integrated with the Desmos application to enhance students’ mathematical abilities. This study aimed to examine the effect of problem-based learning assisted by the Desmos application on students’ mathematical abilities in the topic of quadratic functions. The research employed a quantitative approach using an experimental method involving 32 tenth-grade students. The research instrument consisted of a test in the form of a pretest and a posttest. After obtaining the pretest and posttest data, data analysis was conducted using a t-test. The results indicated a difference in students’ scores before and after the implementation of problem-based learning on quadratic function material using the Desmos application. These findings suggest that problem-based learning integrated with technological tools is effective in improving students’ mathematical abilities.